Treatment of macular hole retinal detachment. - Lai, Y.K. (BMJ Publishing Group, 1990)
Seven patients with macular hole retinal detachment were treated by intravitreal gas injection with or without release of subretinal fluid. Macular buckling, diathermy, cryopexy, or vitrectomy were not used. The patients were placed prone for eight hours a day until the gas had absorbed. In five of the seven patients the retina became reattached within three days and remained reattached with follow-up periods of three to 22 months (average nine months). It is believed that such detachments are due to vitreoretinal traction and the intravitreal gas bubble relieves this traction. This technique is simple, safe, and does not require costly or sophisticated instruments. It has an added advantage in preserving macular function.